PENGARUH BUDAYA ORGANISASI DAN KOMITMEN KERJA TERHADAP KINERJA KARYAWAN (Studi Pada Modern Bakery) - Arum fitria ningsih; Muhyiddin Zainul Arifin (Fakultas Ekonomi Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2021)
The purpose of this study was to analyze the effect of organizational culture and work commitment on employee performance at Modern Bakery. This type of research is quantitative research with survey research methods. In collecting data using purposive sampling technique. The population of this study were employees at Modern Bakery, so the sample in this study was 52 respondents. To analyze the data obtained using the Classical Assumption Test, Multiple Linear Regression and Correlation Coefficient Test using the F test (simultaneous test), T test (partial test). Meanwhile, data collection was carried out through several techniques, namely field studies and lift deployment studies. The results of the research and data processing show that the two independent variables, namely organizational culture and work commitment, simultaneously have a significant effect on employee performance. The correlation coefficient test results show that the R value is 0.864, meaning that organizational culture and work commitment together have a very strong relationship to employee performance. While the results of the coefficient of determination test show that the value of R2 is 0.746, then the value of R2 < 1 means that 74.6% of employee performance at Modern Bakery is influenced by organizational culture and work commitment. While the rest (25.4%) is influenced by other variables outside the study.